Direct light-driven electrodeposition of Bi and Cu without external voltage: Light-induced metal recovery and energy conversion. (December 2022) - Li, Yuewen; Zhang, Yu; Hou, Xing; Lin, Chunkun; Bu, Degang; Lan, Yalin; Li, Na; Wu, Shuyao; Li, Shuo; Song, Xi-Ming
Abstract: Seeking novel solar energy utilization and conversion methods has always been a frontier topic in energy research. Here, we propose a new way to directly photoelectrodeposit metals using solar energy based on semiconductor energy band theory. Three kinds of semiconductor photoanodes (TiO2, BiVO4 and Fe2 O3 ) are employed to deposit metallic Cu or Bi at the cathode under illumination without external voltage. It is found that when TiO2 and BiVO4 are used as photoanodes, Cu, Cu2 O and Bi can be continuously deposited on the cathode, but when Fe2 O3 photoanode is irradiated, no material comes out. The results prove that the potential of electrons in the conduction band determines whether photoelectric deposition occurs or not. The related mechanism involves the oxygen reduction reaction (OER) of the valence band holes of the photoanode, the collection of conduction band electrons by back electrode, as well as the reduction of metal ions on the counter electrode. In addition, we also put forward the concept of using the deposited Cu or Bi as the metal electrode to form a new metal-air battery to release chemical energy of the deposited metal. Graphical abstract: Image 1 Highlights: Cu and Bi are directly deposited by a photoelectrochemical cell without bias. The charge transfer mechanism of photoelectric deposition metals is studied. A new type of Cu/Bi-air battery is proposed. A new energy conversion system is built.